Pendataan Warga Desa Waharia Berbasis Web - Natalia Natalia; Ester Ayuk Pusvita (Jurnal Teknologi dan Informatika, 2024)
The Field Work Practice (PKL) conducted by students of STMIK Pesat Nabire at the Waharia Village Office, Nabire Regency, Central Papua Province, aims to develop and implement a web-based citizen data collection system. This activity is driven by the need for an efficient and integrated data collection system to facilitate administrative processes and public services in Waharia Village. The developed web-based data collection system is designed to record demographic information, residential status, and other essential data of village residents. The development process involves needs analysis, system design, software implementation, and training for village officials. The results of this PKL show that the web-based data collection system can improve the accuracy and speed of data processing, minimize errors in manual recording, and facilitate information access for relevant parties. It is hoped that with this system, work efficiency at the Waharia Village Office will increase, public services will improve, and citizen data will be managed more securely and structurally. This system is also expected to serve as a model for other villages in Nabire Regency in adopting information technology for village administration management.